CAP2 mutation leads to impaired actin dynamics and associates with supraventricular tachycardia and dilated cardiomyopathy. Issue 4 (5th December 2018) - Aspit, Liam; Levitas, Aviva; Etzion, Sharon; Krymko, Hanna; Slanovic, Leonel; Zarivach, Raz; Etzion, Yoram; Parvari, Ruti
Abstract : Background: Dilated cardiomyopathy (DCM) is a primary myocardial disease leading to contractile dysfunction, progressive heart failure and excessive risk of sudden cardiac death. Around half of DCM cases are idiopathic, and genetic factors seem to play an important role. Aim: We investigated a possible genetic cause of DCM in two consanguineous children from a Bedouin family. Methods and results: Using exome sequencing and searching for rare homozygous variations, we identified a nucleotide change in the donor splice consensus sequence of exon 7 in CAP2 as the causative mutation. Using patient-derived fibroblasts, we demonstrated that the mutation causes skipping of exons 6 and 7. The resulting protein is missing 64 amino acids in its N-CAP domain that should prevent its correct folding. CAP2 protein level was markedly reduced without notable compensation by the homolog CAP1. However, β-actin mRNA was elevated as demonstrated by real-time qPCR. In agreement with the essential role of CAP2 in actin filament polymerization, we demonstrate that the mutation affects the kinetics of repolymerization of actin in patient fibroblasts. Conclusions: This is the first report of a recessive deleterious mutation in CAP2 and its association with DCM in humans. The clinical phenotype recapitulates the damaging effects on the heart observed in Cap2 knockout mice including DCM and cardiac conduction disease, but not the other effects on growth, viability, wound healing and eye development. Our data underscore the importance of the proper kinetics of actin polymerization for normal function of the human heart.